PENCIPTAAN MANUSIA DALAM PERSPEKTIF AL QUR’AN DAN SAINS - Rahel Abduh; Ilyas Ibnu Sabi; Albantani Garda; Alhilal Hamdi; Andi Rosa (CV. Adiba Aisha Amira, 2026)
This text provides a scientific explanation of how humans were created by combining the perspectives of the Qur’an and science. The Qur’an explains in detail how humans were created from clay, after which a soul was breathed into them, as described in several verses. On the other hand, modern science explains how humans were created through the theories of evolution, genetics, and embryonic development. This study examines the compatibility between these two perspectives, emphasizing the role of each in understanding the origin and nature of human beings. By examining the verses of the Qur’an from a scientific perspective, this paper aims to demonstrate that there is an opportunity for constructive dialogue between religion and science, as well as how the two can complement each other in explaining the process of human creation. The results show that even though we use different methods, we can still achieve a comprehensive understanding of creation by combining spiritual and scientific knowledge.